Analyzing Customer Satisfaction Using the Kano Model: A 7Ps Marketing Mix Perspective - Muliawati, Elisa Cahya; Ratnawati, Kusuma (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – The objective of this research is to identify the needs and desires of customers of Cahya Alam construction material store as well as their satisfaction to each service attribute referring to the 7Ps marketing mix using Kano Model approach.   Design/methodology/approach – The data of this quantitative study was harvested from interviews and Likert-scaled questionnaires consisting of 22 functional and 22 nonfunctional statements. From the sample of customers of Cahya Alam, 120 of whom were selected as the sample through non-probability sampling method and purposive sampling technique. The data from the questionnaires were initially examined through validity and reliability tests in SPSS version 25.  Findings – The results were then analyzed utilizing the Kano Model, whose results indicate that attributes needing optimization are goods variations, discount availability, information availability for goods price via WhatsApp, more reliable and faster service process, and employees who position themselves as customer service staff.  Originality/value – This study uniquely integrates the Kano Model with the marketing mix to identify priority service attributes for improving customer satisfaction and competitiveness at Cahya Alam.